Daniela Rea, Valeria Luiselli and Jazmina Barrera: The Joy of Motherhood - Vivero, Elizabeth (Advances in Social Sciences Research Journal, 2023)
In Mexican literature, young female writers refer to motherhood from a critical stance, featured as an incident that negatively alters and transforms the lives of the main characters. Amidst this maternal universe, nonetheless, some voices poise a different perspective, conceiving motherhood as a condition that entails joy and bliss. Such is the case of Daniela Rea in “Mientras las niñas duermen”, Valeria Luiselli in Los ingrávidos, and Jazmina Barrera in Línea Nigra, where the writers accomplish setting forth a maternal-filial relationship that is more pleasant, inclined towards a balance between the family and professional life, without setting aside motherhood’s exhaustive aspects. This article will study such texts from a feminist perspective, aiming to demonstrate there is a paradigm shift on how Mexican female writers born from 1980 onwards conceive motherhood.